ANALISIS PENGARUH INVESTASI ASING ATAS SBI DAN INFLASI TERHADAP KURS - Trisnawati Pangaribuan (Department of Development Economics, Universitas Sriwijaya, 2012)
The objective of This research was to analyze the influence of foreign investments toward SBI and inflation rate to exchange rate in Indonesia. This research used data of time series from February 2004 until October 2010 and also used Ordinary Least Square (OLS) method to estimate the exchange rate of rupiah/US in Indonesia. The result showed that foreign investment toward SBI and inflation was one of the factors which influence Exchange value of Rupiah/US in Indonesia. There was also a significant influence between foreign investment toward SBI and Inflation, therefore, it can be used as government reference in deciding monetary policy. Keywords: Exchange Rate Rupiah/US, Inflation, Foreign Investment of SBI, Ordinary Least Square (OLS)